Do equalisation payments affect subnational borrowing? Evidence from regression discontinuity - Monika Köppl-Turyna; Hans Pitlik (Austrian Institute of Economic Research (WIFO), 2016)
According to the fiscal federalism literature sub-central budget constraints become softer when local governments are more dependent on revenues over which they have no discretion. As a consequence of higher "transfer dependency", sub-central governments can expect to be bailed out by the central government and therefore tend to accumulate higher levels of debt. We test this conjecture with data from Austrian municipalities. Austria is a fiscally highly centralised federation in which tax autonomy at the sub-central level is almost absent. Our identification strategy is based on a discontinuity caused by a special regulation on population weights in the tax sharing agreement between central government and the municipalities. We analyse the discontinuity in the conditional expectation of borrowing given population size to unveil an average causal effect of the treatment. Our results indicate that in line with theoretical expectations municipalities with higher revenue dependency observe higher net borrowing per capita. We also find that almost one half of the observed discontinuity works through an investment channel. Net borrowing is spatially correlated.
Keywords: D72; D78; H74; H77; 330; fiscal autonomy; subnational borrowing; vertical fiscal imbalance; regression discontinuity